Technical Aspects and Considerations of Meso-Rex Bypass Following Liver Transplantation With Left Lateral Segment Grafts: Case Report and Review of the Literature - Dalzell, Christina; Vargas, Paola A.; Soltys, Kyle; Di Paola, Frank; Mazariegos, George; Goldaracena, Nicolas (Frontiers in Pediatrics, 2022)
In pediatric patients with extrahepatic portal vein obstruction (EHPVO) and complications of portal hypertension, but with normal liver function, a meso-rex shunt (MRS) connecting the SMV to the intrahepatic left portal is the favored surgical management. Pediatric patients with a history of a partial liver transplant (LT), especially living donor, are especially at risk for portal vein complications. Hence, adequate knowledge of this technique and its additional challenges in the post-liver transplant patient setting is crucial. We provide an overview of the available literature on technical aspects for MRS post-LT. Preoperative considerations are highlighted, along with intraoperative considerations and postoperative management. Special attention is given to even more demanding aspect of performing a meso-rex shunt post-liver transplantation with a left lateral segment. Surgical alternatives are also discussed. In addition, we report here a unique case in which this surgical technique was performed on a complex pediatric patient with a history of a living donor liver transplant with left lateral segment graft over a decade ago.